Strategies for Improving Teacher Professionalism in Madrasah Tsanawiyah (Strategi Peningkatan Profesionalisme Guru di Madrasah Tsanawiyah) - Hadia, Gunawan; Samrin, Samrin (Shautut Tarbiyah-IAIN Kendari, 2024)
Educational success cannot be separated from the efforts of the school principal as a leader in directing and motivating teachers. This research aims to reveal the leadership strategies of school principals in increasing teacher professionalism. This research uses a descriptive qualitative approach. Data sources include teachers and school principals, while data collection uses interview techniques, documentation and observation. The analysis uses continuous participatory techniques, through the stages of data collection, presentation reduction, and drawing conclusions. The results of this research are: This research shows that the role of school principals in increasing teacher professionalism is supervision of teachers, involving teachers in workshop activities, and implementation of the independent curriculum. The principal's strategy for increasing teacher professionalism is giving rewards to teachers who have good performance, providing recommendations related to competency development to take the principal candidate test to teachers who have good performance. Obstacles for school principals in increasing teacher professionalism are the lack of facilities and infrastructure, low teacher incentives, poor behavior of some students towards teachers who teach in class.Keywords: Principal Strategy, Increasing Teacher Professionalism